Treatment of sarcopenia in nursing home residents: a scoping review protocol - Benzinger, Petra; Bauer, Jürgen M.; Schwenk, Michael; Grund, Stefan; Goisser, Sabine (BMJ open, 2020)
Introduction Sarcopenia has been recognised as a disease that is consistently associated with a range of geriatric syndromes and negative health consequences. The prevalence of sarcopenia is high among nursing home residents. Several systematic reviews have assessed the efficacy of a range of treatment strategies against sarcopenia. However, no systematic review discussing specifically the treatment options for sarcopenic nursing home residents has been conducted so far. The objective of this scoping review, therefore, is to identify and map existing studies that assessed the feasibility and effectiveness of interventions that were conducted with the aim to treat sarcopenic nursing home residents. - Methods and analysis The protocol was developed using an established scoping review methodological framework. A systematic search of relevant literature databases will be conducted. We will also conduct a search of ClinicalTrials.gov and the WHO International Clinical Trials Registry Platform Search Portal for ongoing and recently completed trials, and will search for grey literature. Two reviewers will independently screen titles and abstracts for inclusion, followed by screening of the full text of potentially relevant articles to determine final inclusion. A data extraction sheet will be developed including key study characteristics that will be relevant for collating, summarising and reporting the results of the scoping review. - Ethics and dissemination The proposed scoping review will undertake a secondary analysis of publicly available data, and therefore does not require ethical approval. The results will be disseminated to researchers in the field by submitting the review to a peer-reviewed international journal and by presenting our findings at relevant conferences. We expect that the results of the final review will help to guide future research in the field of sarcopenia treatment for nursing home residents.